Rural Development: Motivational Factors Impacting Community Support for Rural Tourism - Marcela Pimid; Azizan Marzuki; Joanna Scian; Kumara Thevan Krishnan (Malaysia Institute of Planners, 2023)
Rural tourism has emerged as a viable domestic tourism option and a means of raising the standard of living and enhancing the environment for rural residents. Successful rural tourism greatly depends on rural tourism products and the local communities residing in particular areas. This study examines factors that influence rural community support for developing tourism in remote areas. The theoretical concept is framed by integrating social exchange theory with social representation theory. It employs a case study approach by examining multiple stakeholder views located in remote Kinabatangan, Sabah. Using a mixed method approach and four labels of data convergence, the findings reveal conflicting views among the stakeholders pertaining to Indigenous motivation and participation in rural tourism activities. The study highlights employing a comrade approach to encourage aboriginal participation in tourism ventures, not merely depending on monetary incentives and tourism awareness campaigns.